Odroczenie wykonania kary ograniczenia wolności - Mrozek, Kamila (Wydawnictwo Uniwersytetu Wrocławskiego, 2012)
The article focuses on the execution of the penalty of restriction of liberty, both in civilian and military law enforcement. The author discusses the rules of compulsory labour and differences in the execution of both forms of the restricted liberty penalty. She gives particular attention to the deferment of the penalty in question, and carries out a thorough analysis of optional and obligatory conditions that make it possible for a convicted person to exercise such a measure.
Keywords: żołnierz służby zasadniczej; kara ograniczenia wolności; odroczenie wykonania kary ograniczenia wolności; dowódca jednostki wojskowej